Vitiligo nonsurgical treatment: a review of latest treatment researches. Issue 5 (12th July 2014) - Zhang, Yanfei; Mooneyan‐Ramchurn, Jessini Soranambal; Zuo, Nan; Feng, Yiguo; Xiao, Shengxiang
Abstract Vitiligo is a common depigmenting acquired disorder affecting about 1–2% of the world population, regardless of race, ethnic background, or gender. It is characterized by the appearance of milky white maculae because of a loss of melanocytes. The disfiguring nature of vitiligo causes high psychosocial morbidity. This is especially pronounced in populations with darker skin tone, likely because of the marked contrast. A variety of nonsurgical treatment regimens are currently employed in vitiligo. We reviewed the latest studies carried out on different nonsurgical treatment modalities used in vitiligo. All nonsurgical treatment aid to repigment or depigmentation the skin, however, many of them require a prolonged treatment course and may yield minimal results as well as carry unwanted side effects. There is a need for further research into the causes of vitiligo and into discovering better treatments.